From Interest to Understanding: The Connection between Reading Interest and Reading Comprehension among Elementary Students - Anak Agung Istri Yudhi Pramawati; Dewa Ayu Ari Wiryadi Joni (Journal on Studies in English Language Teaching (JOSELT), 2026)
Reading is a fundamental skill that plays a crucial role in students’ academic success and language development. Students with a strong interest in reading are more likely to engage in reading activities, which may contribute to better reading comprehension. This study aimed to explore the relationship between reading interest and reading comprehension among elementary school students. The study employed a quantitative correlational research design. Data were collected using two research instruments: a reading interest questionnaire to measure students’ levels of reading interest and a reading comprehension test to assess their comprehension ability. The participants of the study were fifth-grade elementary school students selected through a random sampling technique. The collected data were analysed using descriptive statistics and Spearman Rank correlation analysis after meeting the necessary statistical assumptions. The findings revealed a significant positive relationship between reading interest and reading comprehension. Students with higher levels of reading interest tended to demonstrate better reading comprehension performance. These findings suggest that fostering students’ interest in reading may contribute to the improvement of their reading comprehension skills and support literacy development at the elementary school level.